Miniaturized Cardiovascular Devices: Advancements in Battery-Free Powering Systems - Somashekharayya Hiremath (North American Journal of Engineering Research, 2025)
Miniaturized cardiovascular implants used for patients with arrhythmias and other cardiac conditions provide life-saving interventions and are capable of leadless pacemakers and diagnostic sensors. These devices have traditionally depended on embedded batteries with limited useful life, which require periodic surgical replacement. Inductive coupling, ultrasound-based energy transfer, biomechanical energy harvesting, and recent developments in power systems are able to extend the device's operating time and decrease the need for surgery as well as patient discomfort. This paper describes the engineering principles that make battery-free device functionality work and discusses challenges in power efficiency, compatibility, and device scale integration. This review provides detailed insight into how next-generation cardiovascular implants will be able to have extended lifetimes and be less invasive based on the latest technological advances.